Cast-cap splint in the management of medication-related osteonecrosis of the jaw. Issue 4 (May 2017) - Markose, G.; Graham, R.M.
Abstract: We describe the management of a pathological fracture in a patient with medication-related osteonecrosis using a cast-cap splint. In selected cases this is a simple solution to what can be a difficult condition to treat.